A Prospective Study of Lumbar Facet Arthroplasty in the Treatment of Degenerative Spondylolisthesis and Stenosis: Early Cost-effective Assessment from the Total Posterior Spine System (TOPS™) IDE Study - Jared D. Ament; Amir Vokshoor; Yaser Badr; Todd Lanman; Kee D. Kim; J. Patrick Johnson (Journal of Health Economics and Outcomes Research)
# Background Given the increased attention to functional improvement in spine surgery as it relates to motion preservation, activities of daily living, and cost, it is critical to fully understand the healthcare economic impact of new devices being tested in large FDA randomized controlled trials (RCT). The purpose of this analysis was to comprehensively evaluate the cost-effectiveness of the novel Total Posterior Spine (TOPS™) System investigational device compared with the trial control group, standard transforaminal lumbar interbody fusion (TLIF).